2022
DOI: 10.3389/fpsyg.2022.918488
|View full text |Cite
|
Sign up to set email alerts
|

Exploring a Structural Model of Teaching Enjoyment, Teacher Self-Efficacy, and Work Engagement

Abstract: Due to the complexity of teaching, determining the variables influencing teachers’ work engagement is a rewarding research area. In line with this research agenda, the purpose of this study was to test a structural model of work engagement based on teacher self-efficacy and teaching enjoyment among English as a foreign language (EFL) teachers. For this purpose, 315 Iranian English instructors completed an online survey. Initially, the measurement models for the three latent variables were averred via conductin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 83 publications
3
17
0
Order By: Relevance
“…First, teaching enjoyment was found to be a significant predictor of a teachers' work engagement, supporting Hypothesis 1. This finding is in line with the outcomes reported by previous researchers (e.g., Ouweneel et al, 2012;Datu et al, 2022;Elkheloufi and Yean, 2022;Xiao et al, 2022) who demonstrated that positive emotions including feeling of joy and pleasure play a crucial role in affecting work engagement. The contribution of the teaching enjoyment to teachers' engagement can be interpreted with regard to the fact that teachers who do not get bored, feel pleasure in the class, and enjoy the good atmosphere of the class are more likely to be engaged in their teaching activities (Burić and Macuka, 2018).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…First, teaching enjoyment was found to be a significant predictor of a teachers' work engagement, supporting Hypothesis 1. This finding is in line with the outcomes reported by previous researchers (e.g., Ouweneel et al, 2012;Datu et al, 2022;Elkheloufi and Yean, 2022;Xiao et al, 2022) who demonstrated that positive emotions including feeling of joy and pleasure play a crucial role in affecting work engagement. The contribution of the teaching enjoyment to teachers' engagement can be interpreted with regard to the fact that teachers who do not get bored, feel pleasure in the class, and enjoy the good atmosphere of the class are more likely to be engaged in their teaching activities (Burić and Macuka, 2018).…”
Section: Discussionsupporting
confidence: 92%
“…Their findings indicated that resilience was a strong predictor of FLTE. In another study, Xiao et al (2022) tested a structural model of work engagement, self-efficacy, and teaching enjoyment among 315 EFL instructors. Their findings demonstrated that both predictors affected teachers’ work engagement, although teacher self-efficacy turned out to be a more powerful predictor than teaching enjoyment.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…First, teacher self-efficacy was one of the three direct and significant predictors of FLTE. This finding supports Xiao et al (2022) who reported a significant association between teaching enjoyment and selfefficacy. This outcome also partially supports Burić and Moe (2020), who found an association between teacher self-efficacy and teaching enthusiasm.…”
Section: Discussionsupporting
confidence: 88%